The So-called "eucalyptus Hybrid of Mysore Origin" - Qureshi, I. M. (Indian Forester, 1966)
After an extensive field study of the plantations of the so-called "Eucalyptus Hybrid of Mysore Origin" and the parental stock of this eucalypt, it can now be said with some basis that most of the population in the recent plantations of this eucalypt raised in various States consists of Eucalyptus terelicornis, even one can say to the extent of 99%, the rest being mostly a mechanical mixture of stray plants of E. rabusta, and sometimes of E. camaldulenis, E. botryoides and E. melliodora which however need confirnlation. The species exhibits great polymorphism in both shape and size of leaves and hence the plants are liable to be mistaken as variants of a hybrid population. The growth in the plantations does not exhibit the intermediate forms between the parents which a re supposed to be in combination, viz, E. terelicomis, E. robusta E. botryoides and E. camaldulensis. However, progeny trials on a systematic basis are necessary to confirm this. It is also necessary to compare the growth of the so-called Eucalyptus hybrid of Mysore origin with pure certified seeds of E. tereticornis and also E. camaldulensis, both of which occur under widely varying climatic and edaphic conditions in Australia, and suitable provenances of which will be of great value for future work in India. Also, there will be a great advantage to establish seed orchards or seed plots for each State from the plantations already raised , retaining the stems which have grown best. The observations are also based on the discussions the author had with Prof. L.D. Pryor of Australia during his visit to India in Jan-Feb. 1966 when he undertook a short tour of Nandi Hills (Mysore), Bangalore and Ootacamund with the author. Prof. L.D. Pryor felt pretty confident that the "Mysore hybrid" as generally planted mostly E. tereticrnis, even to the extent of 99%.